Case Reports: Three cases of autoimmune glial fibrillary acidic protein astrocytosis in disguise - Zhao, Wen; Gong, Luyao; Wang, Junbin; Chen, Zhiguang; Li, Zhe; Su, Qiaozhen; Shen, Youbi; Zheng, Chunye (Frontiers in Immunology, 2025)
Autoimmune glial fibrillary acidic protein astrocytosis (GFAP-A), a novel inflammatory autoimmune disorder of the central nervous system, manifests with insidious onset and demonstrates protean clinical manifestations, which frequently leads to diagnostic ambiguity in early disease stages. We describe three typical GFAP-A cases exhibiting multisystem neurological involvement. Our observations show that GFAP-A frequently clinically mimics tuberculous meningitis (TBM), autoimmune encephalitis (AE), neuromyelitis optica spectrum disorder (NMOSD), Parkinson’s disease (PD), and other neurological diseases. Notably, isolated ataxia is a rare presentation in GFAP-A, which allows us usually to consider spinocerebellar ataxia (SCA). Currently, no established diagnostic criteria or standard treatment protocols exist for GFAP-A. Patients with GFAP-A respond well to corticosteroid therapy. We found detecting GFAP-IgG in cerebrospinal fluid or serum is essential for differentiation.